Prevalence of Aeroallergens in Allergic Rhinitis in a Tertiary Care Hospital - Pokharel, Monika (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: The prevalence of allergic rhinitis has increased significantly globally over the last two decades. Detection of sensitizing aeroallergens plays a crucial role in the diagnosis and management of this troublesome disease. This study aims to investigate the spectrum of aeroallergens sensitization in patients with allergic rhinitis in a tertiary care hospital. METHODS: A descriptive cross-sectional study conducted in the Department of Otorhinolaryngology of our hospital between January 2016 to December 2019. Ethical approval was taken from the Institutional Review Committee (No: 210/19). Patients diagnosed with allergic rhinitis were enrolled using the convenience sampling technique. Data entry and analysis was done using IBM Statistical Package for Social Sciences version 20.0. RESULTS: Among 170 patients, altogether 103 (60.6%) patients yielded positive responses on the skin prick test. The most prevalent aeroallergens were Lepidoglyphus 86 (50.60%), Dermatophagoides pteronyssinus 85 (50%), Dermatophagoides farina 82 (48.20%), Thyrophagus 50 (29.40%), Blomia 46 (27.10%), Acarus 43 (25.30%), cat dander 26 (15.30%), dog dander 24 (14.10%), cow and buffalo dander 20 (11.8%), ragweed 20 (11.8%), grass pollen 18 (10.60%) and mugwort 17 (10%). CONCLUSIONS: This study highlights that the frequency of aeroallergens based on skin prick test in patients presenting to a tertiary care hospital which showed the dominance of house dust mites, dog and cat hair, pollen, and grasses. Reduced exposure and training of patients about protection against these agents will possibly help in controlling the severity of allergic rhinitis in this region.